Pengaruh Kepemimpinan Transformasional, Work-Life Balance dan Pengembangan Karir Terhadap Retensi Milenial dan Gen-Z Melalui Kepuasan Kerja - Syintia Mega Putri; Figo Alimbel; Ramadhana Aulia Wisdawati; Jodi Septiadi Akbar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study was conducted to examine the influence of Transformational Leadership, Work-Life Balance, and Career Development on Millennial and Gen-Z Retention through Job Satisfaction among banking employees in Pekanbaru City. The study used a quantitative approach. Quantitative data were obtained by distributing questionnaires to 100 Millennial and Gen-Z banking employees and analyzed using the Smart PLS 4 data processing system. The results showed that Transformational Leadership (β = 0.241; p = 0.004) means that Transformational Leadership has a positive and significant effect on Job Satisfaction, Work-Life Balance (β = 0.386; p = 0.000) means that Work-Life Balance has a positive and significant effect on Job Satisfaction, and the influence of Career Development (β = 0.419; p = 0.000) has a positive and significant effect on Job Satisfaction. Job Satisfaction was proven to have a very significant effect on Employee Retention with a path coefficient of (β = 0.567; p = 0.000). For the indirect influence of the mediation variable, it shows that Leadership has a positive and significant indirect influence on employee retention through Job Satisfaction with a coefficient value of 0.137. Then the Work-Life Balance variable shows a positive and significant indirect influence on employee retention through job satisfaction with a coefficient value of 0.219. And finally, Career Development has the greatest indirect influence on employee retention through job satisfaction with a coefficient value of 0.238. For the influence of Career Development, it is the variable with the highest level of results in increasing job satisfaction, followed by Work-Life Balance and Transformational Leadership. These findings provide practical implications for banking management to develop comprehensive retention strategies and policies with a focus on sustainable career development, work flexibility, and an inspirational leadership style to retain high-potential employee talent in the company.